Case Report: The unique case of flexible intramedullary nailing of pediatric radius complicated with temporary radial nerve’s motor branch damage - Wiktor, Łukasz; Tomaszewski, Ryszard (Frontiers in Pediatrics, 2024)
This study reported a case of radius flexible intramedullary nailing complicated by temporary paralysis of the posterior interosseous nerve due to compression of the ESIN on the nerve in an 8-year-old boy. The nerve damage resulted from an essential misconception at the surgery. Despite bad decisions made during qualifications and the procedure undertaken, restoring the nerve function, and gaining satisfactory functional fracture recovery was possible. Although it is generally acknowledged to perform retrograde flexible intramedullary nailing from the level of the distal radial metaphysis, the presentation of our case aims to emphasize the real risk of damage to the motor branch of the radial nerve when approaching the proximal metaphysis.